Proposta metodológica para a avaliação ex-ante dos impactos de intervenções no transporte público nas desigualdades socioespaciais no acesso a atividades - Freire, Renan Monteiro Carioca (2019)
The practice in evaluation of transport projects occurs mainly through a Cost-Benefit Analysis (CBA) of the analyzed solution, in which the underlying principles are the utilitarianism and the individuals’ willingness to pay for the intervention. This theoretical framework is, in turn, criticized by the state-of-the-art literature in transportation planning due to having biases which culminate in reinforcing socio-spatial inequalities in the urban environment, leading to conditions of social exclusion specially in the most socially vulnerable groups of individuals. This understanding, whose core lies in the nexus between transportation supply and social inclusion, relies in equity as a guiding principle for the planning process, as well as the concept of access to activities in order to represent the welfare to be promoted to the individuals, acknowledging that all must have a minimum level of accessibility in order to interact with opportunities and basic services, as well as seeing all inequalities among social groups as distortions to be corrected. In this context, some methodological limitations are pointed out, referring to how the evaluation process is aligned with this theoretical framework, where this work aims to contribute both in how the impacts are analyzed, by arguing for a diagnosis phase previous to the assessment itself, and also how accessibility itself is measured, making the evaluation process more reliable and theoretically sound. Finally, the proposed method is applied to the implementation of temporal integration in Fortaleza’s urban bus system, assessing how it impacts in mitigating socio-spatial inequality problems on access to jobs in the city.